Physicochemical Characterization and FTIR Analysis of Galactomannan from Sugar Pulm Fruit (Arenga pinnata Merr.) - Ihsan, Fikratul; Anggraini, Anna (Yayasan Rahmatan Fiddunya Wal Akhirah, 2023)
Commercial galactomannans such as guar gum, tara gum and locust bean gum are used as thickeners and emulsion stabilizers in the food industry. The increasing demand of the food industry for galactomannan has become the focus of research to developed from other plant sources such as sugar pulm fruit. Galactomannan was successfully extracted from kolang-kaling based on the structural characteristics of galactomannan which confirmed the presence of α and β conformers at wave numbers 810 and 871 cm-1. The physicochemical characterization in this study include yield, specific gravity, pH, soluble protein content, moisture content, water absorption and oil absorption. Based on the results of this study, the yield of galactomannan sugar pulm fruit was 2.33% with a specific gravity of 1.00 g/ml. Galactomannan of sugar plum fruit has pH, soluble protein content, water content, water absorption and oil absorption significantly different from tara gum. The water absorption and oil absorption capacity of galactomannan is higher than tara gum, so it can be used as a thickener and emulsion stabilizer to replace commercial galactomannan.